Use of Drotaverine 80mg with Paracetamol 500mg in Patients with Acute Bacterial Gastroenteristis - Syed Hassan Musanna, Mounis Ahmad Zaffar, M Abdullah, Javaria Amil, Sheraz Saleem (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study’s goal is to see whether drotaverine 80 mg and paracetamol 500 mg are as effective and safe as each other in treating individuals with acute gastroenteritis. Study Design: Randomized control trial Place and Duration: The study was conducted at the medicine department of Lahore General Hospital and Ittefaq Hospital Trust, Lahore for the period of five months from April 2021 to August 2021. Methods: Total one hundred and eighty patients of both genders with ages 17-60 years were presented. Patients had acute infectious gastroenteritis with abdominal pain from last 24 hours were included. To obtain comprehensive demographic information, including age, gender, height/weight, and BMI (body mass index), informed written permission was obtained from each patient. A total of two groups of patients were created: I and II. It took two days to provide 80mg drotaverine, together with 500 mg paracetamol, to patients in group I, while it took two days to administer 500 mg paracetamol, along with the same number of patients, in group II. A visual analogue scale (VAS) was used to measure the severity of pain in both groups after treatment to determine efficacy and safety. SPSS 24.0 was used to analyze the data. For categorical data, frequency and percentage were employed. Results: Mean age of the patients in group I was 30.07±4.28 years with mean BMI 23.07±4.32 kg/m2 and in group II 28.17±9.88 years was the mean age with mean BMI 22.44±8.21 kg/m2. Majority of the patients were males 59 (65.6%) in group I and 54 (60%) in group II. Intensity of pain was significantly decreases after 8hrs in group I 1.01±2.17 as compared to group II 4.09±11.34. Post treatment effectiveness among patients in group I was 84 (93.3%) greater than that of group II 54 (60%). The most prevalent side effects in both groups were nausea, vomiting, and dizziness, however the frequency was considerably lower in group I than in group II with a p value of 0.005.Frequency of satisfaction in group I was 88 (97.8%) higher than that of group II 60 (66.7%). Conclusion: In this study we concluded that the combination of 80mg drotaverine with 500mg paracetamol was effective and safe in terms of pain control and control of infection as compared to the paracetamol alone in the treatment of patients with acute gastroenteritis.